Offshoring, wages and job security of temporary workers - Holger Görg; Dennis Görlich (Institute for the Study of Labor (IZA), 2012)
We investigate the impact of offshoring on individual level wages and unemployment probabilities and pay particular attention to the question of whether workers on temporary contracts are affected differently than workers on permanent contracts. Data are taken from the German Socio-Economic Panel (SOEP), linked with industry-level data on offshoring of materials and services inputs calculated from the World Input Output Database (WIOD). In manufacturing we find that temporary workers face a significant reduction in wages as materials offshoring increases, while permanent workers' wages are unaffected or even tend to increase. Offshoring of core activities generally also tends to reduce the probability of becoming unemployed, and more so for temporary than for permanent workers. By contrast, offshoring of services inputs does not have any statistically significant effects on either wages or employment probabilities in manufacturing. In the service industries, workers are affected in terms of employment probabilities from offshoring of services inputs only, although, in contrast to manufacturing industries, there are no statistically significant effects on individual wages from any type of offshoring.
Keywords: J31; F14; 330; offshoring; temporary work; job security; wages; Auslandsverlagerung; Befristeter Arbeitsvertrag; Lohnstruktur; Arbeitsplatzsicherung; Industrie; Dienstleistungssektor; Deutschland